Ultrasound-mediated nanobubble destruction (UMND) facilitates the delivery of A10-3.2 aptamer targeted and siRNA-loaded cationic nanobubbles for therapy of prostate cancer - Meng Wu; Hongyun Zhao; Liang Guo; Yiru Wang; Jiao Song; Xueli Zhao; Chongyan Li; Lan Hao; Dong Wang; Jie Tang (Taylor & Francis Group, 2018)
The Forkhead box M1 (FoxM1) transcription factor is an important anti-tumor target. A novel targeted ultrasound (US)-sensitive nanobubble that is likely to make use of the physical energy of US exposure for the improvement of delivery efficacy to target tumors and specifically silence FoxM1 expression appears as among the most potential nanocarriers in respect of drug delivery. In this study, we synthesized a promising anti-tumor targeted FoxM1 siRNA-loaded cationic nanobubbles (CNBs) conjugated with an A10-3.2 aptamer (siFoxM1-Apt-CNBs), which demonstrate high specificity when binding to prostate-specific membrane antigen (PSMA) positive LNCaP cells. Uniform nanoscaled siFoxM1-Apt-CNBs were developed using a thin-film hydration sonication, carbodiimide chemistry approaches, and electrostatic adsorption methods. Fluorescence imaging as well as flow cytometry evidenced the fact that the siFoxM1-Apt-CNBs were productively developed and that they specifically bound to PSMA-positive LNCaP cells. siFoxM1-Apt-CNBs combined with ultrasound-mediated nanobubble destruction (UMND) significantly improved transfection efficiency, cell apoptosis, and cell cycle arrest in vitro while reducing FoxM1 expression. In vivo xenografts tumors in nude-mouse model results showed that siFoxM1-Apt-CNBs combined with UMND led to significant inhibition of tumor growth and prolonged the survival of the mice, with low toxicity, an obvious reduction in FoxM1 expression, and a higher apoptosis index. Our study suggests that siFoxM1-Apt-CNBs combined with UMND might be a promising targeted gene delivery strategy for therapy of prostate cancer.